UNVEILING ‘PROFIL PELAJAR PANCASILA’ THROUGH A NAS DAILY VIDEO: A CRITICAL EXAMINATION OF CHARACTER EDUCATION VALUES IN DIGITAL NARRATIVES - Arti, Sinta Budhi; Heriyawati, Dwi Fita (University of Kuningan, 2024)
Character education is one of the goals of our National Education System. Teaching character education can be accomplished by various media, one of them is watching inspiring videos. This study explores the character education values implied in a video retrieved from Nas Daily YouTube channel. The character values focused in this study are the six dimensions of ‘Profil Pelajar Pancasila’ in the Merdeka Curriculum. This study uses the model of critical discourse analysis by Teun A. Van Dijk that examines the discourse in three elements; text structure, social cognition, and social context. The findings revealed that the video embraces all of the six dimensions of ‘Profil Pelajar Pancasila’ in the Merdeka Curriculum. This could strengthen the insight of educators to seek more character-empowering shows for the learners.